Grammaticalization as economy - Gelderen, Elly van (Linguistik aktuell, 2004)
This book provides much detail on the changes involving the grammaticalization of personal and relative pronouns, topicalized nominals, complementizers, adverbs, prepositions, modals, perception verbs, and aspectual markers. It accounts for these changes in terms of two structural economy principles. Head Preference expresses that single words, i.e. heads, are used to build structures rather than full phrases, and Late Merge states that waiting as late as possible to merge, i.e. be added to the structure, is preferred over movement. The book also discusses grammar-external processes (e.g. prescriptivist rules) that inhibit change, and innovations that replenish the grammaticalized element. Most of the changes involve the (extended) CP and IP: as elements grammaticalize clause boundaries disappear. Cross-linguistic differences exist as to whether the CP, IP, and VP are all present and split and this is formulated as the Layer Principle. Changes involving the CP are typically brought about by Head Preference, whereas those involving the IP and VP by Late Merge. --